Holy day in a holy place: space, time, and annual miracles in late antique hagiography and the cult of saints - Wiśniewski, Robert (Byzantinische Zeitschrift, 2023)
This article examines hagiographical accounts of miracles that occurred annually at sanctuaries of martyr saints on their feast days. It argues that these accounts, popular in Christian literature of the later part of the first Millennium in both the eastern and western Mediterranean, demonstrate the parallel development and close resemblance between Christian concepts of holy places and holy days. The annual miracles confirmed the saints' powerful presence at specific points in time and space, demonstrating that neither the selection of cult places nor feast days was arbitrary, but reflected God's design. God scattered holy places and holy days throughout the earth and the year in order to add glory to His saints and support His people.